Evaluasi Faktor Penyebab Kegagalan Calon Sekolah Adiwiyata Nasional di Provinsi Sumatera Selatan - Dini Purwaningsih (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Purwaningsih D. 2020. evaluating the Failure Factors of the National Adiwiyata School Candidates in South Sumatra province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Not entirely the Provincial Adiwiyata schools in South Sumatra were nominated for National Adiwiyata school selection achieved the award. This study aims to evaluate the factors that caused the Provincial Adiwiyata School nominees failed to achieved the National Adiwiyata School award. The data in this study were obtained through document study and interviews with Adiwiyata's team, school principals and teachers. This research uses qualitative descriptive analysis technique to analyze the data. Based on the data held by the Environment and Land Office of South Sumatra Province since 2010 until 2019, not all candidates for the National Adiwiyata school from South Sumatra Province have reached the National Adiwiyata school award. According to the interviews with the Adiwiyata team, the principal and teachers, it is indicated that there are several factors causing this failure. They are namely because: first, the National Adiwiyata school candidates forgot to attach the proposal to the Head of the Environment Agency of South Sumatra Province. Second, every school member does not fully understand about the environmental knowledge as well as the lack of school participation in creating a cultured and environmentally friendly school. Thus the author concludes that in order to achieve the National Adiwiyata school award, the nominated Adiwiyata Provincial schools should be re-examined to complete the administrative requirements, socialize the knowledge of environmental care to all school members, and remind all school members to always actively participate in creating a cultured and environmentally friendly school.